An analysis of “appreciation” used in shangri-la dialogue in the appraisal perspectives - Đoàn Thị Thu Hằng (ĐHĐN., 2015)
This study aims to explore the use of Appreciation in Shangri-la Dialogue with an attempt to find a solution for improving Vietnamese learners’ performance in using Appreciation. The research chose to examine Appreciation, one of the three subsystems within the framework of Appraisal theory. The study was conducted based on the descriptive framework of functional grammar and appraisal theory. The data were extracted from transcripts on the website of International Institute for Strategic Studies with 200 samples. The sampling was done with random manner so that every sample has the equal opportunity to occur in the corpus. The data were analyzed and classified into different categories in terms of systactic and semantic features. Syntactically, appreciation was found in theme - rheme structure, adverbial groups and nominal groups in view of functional grammar. Semantically, appreciation was analyzed in terms of appraisal. The study found that speakers/ writers can use appreciation to express their opinion, feeling, and valuation about the issues in Shangri-la Dialogue to listeners/ readers. Based on the analysis of the data collected, some implications were put forward for English language teaching and learning, for translators as well as anyone who are interested in Appreciation in Shangri-la Dialogue.